Isolation, Characterization and Performance of Autochthonous Spray Dried Lactic Acid Bacteria in Maize Micro and Bucket-Silos - Burns, Patricia; Borgo, María F.; Binetti, Ana; Puntillo, Melisa; Bergamini, Carina; Páez, Roxana; Mazzoni, Rodolfo; Reinheimer, Jorge; Vinderola, Gabriel (Frontiers in Microbiology, 2018)
The aim of this study was to isolate, identify and characterize lactic acid bacteria (LAB) from spontaneously fermented maize silage, and evaluate their performance as spray-dried (SD) cultures to enhance the fermentation and the aerobic stability of maize micro-silos. Eleven strains of LAB were characterized for growth kinetics, the capability to grow in vegetable-based medium (VBM), production of organic acids and the ability to tolerate heat–stress. Three strains (Lactobacillus plantarum Ls71, Pediococcus acidilactici Ls72, and Lactobacillus buchneri Ls141) were selected and further characterized for the ability to grow as single strain or in co-culture in MRS and VMB medium, to survive at freeze and spray-drying process, for their performance as SD bacteria in micro-silos and for the aerobic stability in bucket silos. L. buchneri Ls141 showed the highest growth capability in VBM and produced the highest amount of acetic acid, while L. plantarum Ls71 produced the highest amounts of lactic acid. P. acidilactici Ls72 was the most heat-resistant strain, with a reduction of 0.2 log10 CFU/mL (15 min at 55°C). The three strains satisfactorily tolerated both spray and freeze-drying. After 4 days of fermentation, all the samples reached a pH value of about 3.7–3.8. A significantly lower cell load of filamentous fungi and yeasts (< 3 log10 CFU/g) and a higher concentration of total LAB (> 8.7 log10 CFU/g) was observed after 30 days of fermentation. A greater amount of acetic acid, crude protein, ash and ammonia nitrogen/total nitrogen was detected in inoculated silages. A significant reduction of filamentous fungi and yeasts was also observed in inoculated bucket silos after 50 d of fermentation. The aerobic stability was significantly improved in inoculated silage since the temperature remained stable after 16 days (384 h). On the contrary, an increase of 5°C was observed in control samples after 1 day. The selected strains have the potential to be produced as SD silage inoculant as they were able to accelerate the fermentation process, to control filamentous fungi and yeasts, to improve some nutritional and chemical parameters of silage and to improve aerobic stability.